Housing Finance Across Countries : New Data and Analysis - Badev, Anton; Beck, Thorsten; Vado, Ligia; Walley, Simon (World Bank, Washington, DC, 2014)
This paper presents new data on the depth and penetration of mortgage markets across countries. There is a large variation across both dimensions of mortgage market development, across countries, but also -- in terms of depth -- within countries. Mortgage markets seem to develop only at relatively high levels of gross domestic product per capita. Policies associated with financial system development are also associated with mortgage market development, including price stability and the efficiency of contractual and information frameworks. The development of the insurance sector and the stock market, sources of long-term funding, is strongly associated with mortgage market development, while government subsidies and support are not. A benchmarking exercise compares the actual values of mortgage market development to values predicted by structural country factors and shows a large variation across countries and over time in the gap between predicted and actual values, related to specific policies but also mortgage boom and bust cycles.